2017
DOI: 10.5505/pajes.2016.75975
|View full text |Cite
|
Sign up to set email alerts
|

Large neighbourhood search algorithm for type-II assembly line balancing problem

Abstract: Öz This paper proposes a large neighbourhood search (LNS) algorithm for type-II simple assembly line balancing problem (SALBP-II

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Afterward, Trigui extended the base part approach to finding subassemblies for reduction gearbox assembly and the cylinder crimping assembly, where the base part is considered based on more contacts and more volume compared to other parts (Trigui et al, 2015;2017). Unlike the above researchers, Xing examined collision between components during assembly/ disassembly operations (Xing et al, 2007).…”
Section: Base Part Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Afterward, Trigui extended the base part approach to finding subassemblies for reduction gearbox assembly and the cylinder crimping assembly, where the base part is considered based on more contacts and more volume compared to other parts (Trigui et al, 2015;2017). Unlike the above researchers, Xing examined collision between components during assembly/ disassembly operations (Xing et al, 2007).…”
Section: Base Part Methodsmentioning
confidence: 99%
“…The major limitation that existed in the theory of loops, theory of connectors and theory of clusters is their ability to identify the consistency in the established contact. It can be observed that the existed approaches treated the permanent stability with the existence of connection, however, the other possible instances are not considered (Akpinar, 2017;Murali et al, 2019). The subassembly identified at each stage is treated as a single part and tested for their feasibility to offer collision with the remaining parts for the assemblability/disassemblability.…”
Section: Influence Of Predicate Considerationmentioning
confidence: 99%
“…Data set includes seven problems with task numbers differing between 29 and 111: Buxey (29,8,7,14), Sawyer (30,8,7,14), Gunther (35,10,6,15), Kilbridge (45,9,3,11), Tonge (70, 23,3,25), Arcus1 (83,20,3,22), Arcus2 (111,25,3,27). The numbers in the parenthesis indicate the task numbers, the number of test instances contained in the relevant ALBP, minimum and maximum number of workstations of test instances in the relevant ALBP, respectively.…”
Section: Experimental Studymentioning
confidence: 99%
“…Arıkan [28] developed a TS algorithm which uses a diversification strategy based on residence frequencies to solve the type-2 simple assembly line balancing problem with a workload smoothing objective. Akpınar [29] developed a large neighbourhood search algorithm to solve SALBP-2 and evaluated the achievement of the algorithm on a set of test problems. Researchers looking for a more detailed information about the assembly line balancing problems and related studies can refer to Sivasankaran and Shahabudeen [30] and Boysen et al [31].…”
Section: Introductionmentioning
confidence: 99%